The Metaphysics of the Incarnation in Contemporary Analytic Philosophy of Religion - Dobrzeniecki, Marek (Verbum Vitae, 2021)
The paper presents the latest achievements of analytic philosophers of religion in Christology. My goal is to defend the literal/metaphysical reading of the Chalcedonian dogma of the hypostatic union. Some of the contemporary Christian thinkers claim that the doctrine of Jesus Christ as both perfectly divine and perfectly human is self-contradictory (I present this point of view on the example of John Hick) and, therefore, it should be understood metaphorically. In order to defend the consistency of the conciliar theology, I refer to the work of, among others, Eleonore Stump, William Hasker, Peter Geach and Kevin Sharpe. As a result, I conclude that recent findings in analytic metaphysics provide an ontological scaffolding that explains away the objection of the incompatibility of the doctrine of the hypostatic union. In order to confirm this conclusion such metaphysical topics as properties attribution (what it means for an object to have a property), relation of identity (what it means for an object x to be identical with object y), and essentialism and kind membership (what it means for an object to belong necessarily to a kind) are scrutinized in detail.